2009
DOI: 10.1063/1.3159877
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystallization of nanocrystalline silicon microwires through rapid self-heating

Abstract: Extraction of temperature dependent electrical resistivity and thermal conductivity from silicon microwires selfheated to melting temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…During the maximum ac voltage amplitude, a sudden increase in current is observed suggesting that the wire resistance decreases significantly due to onset of wire melting ( Figure 2). 13 The next point shows no measurable current indicating wire breakage. Once the I-V characteristic of a wire is constructed from the V-t and I-t characteristics (Figure 2(a)), the wire is modeled using COMSOL Multiphysics.…”
Section: Methodsmentioning
confidence: 99%
“…During the maximum ac voltage amplitude, a sudden increase in current is observed suggesting that the wire resistance decreases significantly due to onset of wire melting ( Figure 2). 13 The next point shows no measurable current indicating wire breakage. Once the I-V characteristic of a wire is constructed from the V-t and I-t characteristics (Figure 2(a)), the wire is modeled using COMSOL Multiphysics.…”
Section: Methodsmentioning
confidence: 99%
“…Melting is expected to start at one side of the wire due to significant Thomson effect under high current densities [11]- [13]. While the wire is molten, surface tension forces the wire to take a cylindrical form, and the diffusion of silicon from the wire to its contact pads which are at a lower temperature results in thinning of the wire if a pulse duration is sufficient [10]. As the voltage pulse is terminated, the wire begins to solidify starting from 0741-3106/$26.00 © 2010 IEEE its contact pads, keeping its newly acquired geometry.…”
Section: Methodsmentioning
confidence: 99%
“…This same experimental setup, without the load resistor, has been used for experiments on electrical annealing of the wires and growth from melt at a micrometer scale [10]. These microwires can be completely melted with a single 1-μs ∼20-V (E ∼ 25 kV/cm and J ≥ 20 MA/cm 2 ) pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thermal movement of nanowires between the SOI islands and their consequent rupture at temperatures ≥150°C excludes conventional furnace annealing (details of the thermal behavior were investigated by Sainiemi et al [75]). Nevertheless, it was reported that current-driven self-heating processes can be applied to recrystallize Si nanowires [76]. Therefore, to lower the resistivity of the fabricated Nanowires a two terminal set-up providing voltage while measuring the current was used to investigate possible DC annealing.…”
Section: Direct Current Annealingmentioning
confidence: 99%